18F-trifluoromethanesulfinate enables direct C–H 18F-trifluoromethylation of native aromatic residues in peptides - Kee, C; Tack, O; Guibbal, F; Wilson, T; Isenegger, P; Imiołek, M; Verhoog, S; Tilby, M; Boscutti, G; Ashworth, S; Chupin, J; Kashani, R; et al. (American Chemical Society, 2020)
18F-Labeling strategies for unmodified peptides with [18F]fluoride require 18F-prosthetics for bioconjugation more often with cysteine thiols or lysine amines. Here, we explore selective radical chemistry to target aromatic residues applying C–H 18F-trifluoromethylation. We report a one-step route to [18F]CF3SO2NH4 from [18F]fluoride, and its application to direct [18F]CF3-incorporation at tryptophan or tyrosine residues using unmodified peptides as complex as recombinant human insulin. The fully automated radiosynthesis of octreotide[Trp(2-CF218F)] enables in vivo PET imaging.